Carbohydrate recognition by the antiviral lectin cyanovirin-N - Fujimoto, Yukiji K. (2012)
Cyanovirin-N is a cyanobacterial lectin with potent antiviral activity, and has been the focus of extensive pre-clinical investigation as a potential prophylactic for the prevention of the sexual transmission of the human immunodeficiency virus (HIV). Here we present a detailed analysis of carbohydrate recognition by this important protein, using a combination of computational methods, including extensive molecular dynamics simulations and Molecular-Mechanics/ Poisson–Boltzmann/Surface-Area (MM/PBSA) energetic analysis. The simulation results strongly suggest that the observed tendency of wildtype CVN to form domain-swapped dimers is the result of a previously unidentified cis-peptide bond present in the monomeric state. The energetic analysis additionally indicates that the highest-affinity ligand for CVN characterized to date (α-Man-(1,2)-α-Man-(1,2)-α-Man) is recognized asymmetrically by the two binding sites. Finally, we are able to provide a detailed map of the role of all binding site functional groups (both backbone and side chain) to various aspects of molecular recognition: general affinity for cognate ligands, specificity for distinct oligosaccharide targets and the asymmetric recognition of α-Man-(1,2)-α-Man-(1,2)-α-Man. Taken as a whole, these results complement past experimental characterization (both structural and thermodynamic) to provide the most complete understanding of carbohydrate recognition by CVN to date. The results also provide strong support for the application of similar approaches to the understanding of other protein–carbohydrate complexes.